An animal-borne active acoustic tag for minimally invasive behavioral response studies on marine mammals. Issue 1 (December 2016) - Fregosi, Selene; Klinck, Holger; Horning, Markus; Costa, Daniel; Mann, David; Sexton, Kenneth; Hückstädt, Luis; Mellinger, David; Southall, Brandon
Abstract Background There is a variety of evidence that increased anthropogenic noise (e.g., shipping, explosions, sonar) has a measureable effect on marine mammal species. Observed impacts range in severity from brief interruptions of basic life functions to physiological changes, acute injury, and even death. New research tools are needed to better measure and understand the potential effects of anthropogenic noise on marine mammals. Current behavioral response studies typically utilize ship-based sound sources to study potential acute behavioral responses in tagged animals experimentally exposed to noise. Integrating the sound source within animal-mounted passive acoustic and motion-sensing tags provides a novel tool for conducting additional highly controlled response studies. Results We developed and conducted pilot field trials of a prototype tag on five juvenile northern elephant seals, Mirounga angustirostris, using experimental exposures to both natural and anthropogenic noise stimuli. Results indicate behavioral responses were elicited in tagged individuals. However, no pattern was found in the occurrence and types of response compared to stimulus type. Responses during the ascending dive phase consisted of a dive inversion, or sustained reversal from ascending to descending (8 of 9 exposures). Dive inversions following exposure were 4–11 times larger than non-exposure inversions. Exposures received during the descending dive phase resulted in increased descent rates in 9 of 10 exposures. All 8 exposures during dives in which maximum dive depth was limited by bathymetry were characterized by increased flow noise in the audio recordings following exposure, indicating increased swim speed. Conclusions Results of this study demonstrate the ability of an animal-mounted sound source to elicit behavioral responses in free-ranging individuals. Behavioral responses varied by seal, dive state at time of exposure, and bathymetry, but followed an overall trend of diving deeper and steeper and swimming faster. Responses did not consistently differ based on stimulus type, which may be attributable to the unique exposure context of the very close proximity of the sound source. Further technological development and focused field efforts are needed to advance and apply these tools and methods in subsequent behavioral response studies to address specific questions.